THE EFFECT OF BOILED WATER CONCENTRATION OF RED BETEL LEAF (Piper crocatum) ON THE KIDNEY AND PANCREAS HISTOPATHOLOGY OF DIABETIC MICE (Mus musculus) - Kurniasiwi, Putri; Surati, Surati; Armalia, Desi; Farizal, Jon (Fakultas Ilmu Kesehatan, 2023)
Red betel leaves contain flavonoid compounds that can reduce blood sugar levels and minimize tissue damage by reducing lipid peroxide. This study aims to determine the effect of red betel leaf boiled water with a concentration of 25%, 50%, 75% and 100% on the histopathology of the kidneys and pancreas of diabetic mice and to determine the most effective concentration. This experimental research was a completely randomized design with 2 control groups, K+ and K-, and 4 treatment groups, P1, P2, P3 and P4, with a sample population of 18 mice. Experimental animals were treated by giving red betel leaf boiled water with a concentration of 25%, 50%, 75% and 100%, 50 mg and a sonde dose of 0.13 ml for 7 days. Then the kidneys and pancreas were taken, processed histologically and observed with a 400x magnification microscope in 3 fields of view. The results of pancreatic histopathological observations were statistical tests using the Kruskal Wallis followed by the Mann Whitney test showing sig. 0.015 means that the histopathological picture of the pancreas of mice P3, P4 has a significant difference compared to mice in the K (+) group. Concentrations of 75% and 100% resulted in enlargement of kidney cell size approaching the size of healthy kidney cells and there was the best improvement in the pancreas organ. The conclusion is that concentrations of 25%, 50%, 75% and 100% of red betel leaf boiled water affect the histopathology of the kidneys and pancreas of diabetic mice.